The Effectivity of Indigenous Rhizobacteria and Manure on the Yield of Red Potato (Solanum tuberosum L.) - Winda Purnama Sari; Warnita Warnita; Indra Dwipa (JERAMI : Indonesian Journal of Crop Science, 2022)
Potatoes are one of the world's five food crops in the form of tubers and have many benefits. One type of potato developed in Indonesia is red potatoes because they have a high nutritional content and are more susceptible to plant pest organisms. An experiment was conducted in Nagari Selayo Tanang Bukit Sileh, Lembang Jaya, Solok, West Sumatra, Indonesia from May to August 2017. The effect of three indigenous rizobacteria (A2.1b2, A3.1a5 and B1.2a2) and three types of manure, both individually and in combination, on the growth and yield of red potatoes was studied. A two way factorial experiment with a completely randomized design and three replicates was used. Chicken, quail and cattle manure were applied at a dose of 30 tons per hectare. Data were analyzed by analysis of variance and comparison of mean using the Honestly Significant Difference test at the 5% level. There was no interaction between rizobacterial isolates and manure on the growth and yield of red potatoes. All isolates gave similar results with respect to plant growth, but isolates A2.1b2 give the best yields. Chicken manure increased fresh weight of tubers by 11.73 ton per hectare compared to quail and cattle manure.